2021
DOI: 10.1111/imig.12852
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent careers of a resilient mobile workforce: Edu‐immigrants

Abstract: Although the concept of migration and international education is not completely new, the sudden and dramatic expansion of the global education system has created a situation in some western countries in which the growth in international student populations has far outstripped domestic students. For example, the numbers of international students studying in Canada, the United States and the United Kingdom have steadily increased over the past 20 years (Sá & Sabzalieva, 2018). Furthermore, the political, demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…While competencies have been examined in several contexts, such as expatriate (Dickmann et al, 2018), young professionals (Blokker, Akkermans, Tims, Jansen, and Khapova, 2019), employees (Haenggli, and Hirschi, 2020;Sultana and Malik, 2019), women managers (Chen, Doherty, and Vinnicombe, 2012), and academics (Beigi et al, 2018;Sherif, Nan, and Brice, 2020), not much is understood about their starring function in entrepreneurial careers (Zikic and Ezzedeen, 2015). Furthermore, while intelligent career theory has been used in other fields such as academia (Beigi, Shirmohammadi, and Arthur, 2018;, executives (Guptill, Reibling, and Clem, 2018;Lee, 2018), expatriates (Cappellen and Janssens, 2008) and other professionals (Beigi, Nayyeri, and Shirmohammadi, 2020;Blokker, Akkermans, Tims, Jansen, and Khapova, 2019;Haenggli and Hirschi, 2020;Schlosser, Lam, and Kerr, 2021), and mostly found empirical backing for numerous career competencies and relevant resources in influencing career success in all its forms, there is a vacuum about the context of entrepreneurs. This especially refers to knowing whom, why, and how, which are prominent in the new career literature but are glaringly ignored by most research in the entrepreneurship area Crowley-Henry, O'Connor, and Suarez-Bilbao, 2021;Schlosser et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While competencies have been examined in several contexts, such as expatriate (Dickmann et al, 2018), young professionals (Blokker, Akkermans, Tims, Jansen, and Khapova, 2019), employees (Haenggli, and Hirschi, 2020;Sultana and Malik, 2019), women managers (Chen, Doherty, and Vinnicombe, 2012), and academics (Beigi et al, 2018;Sherif, Nan, and Brice, 2020), not much is understood about their starring function in entrepreneurial careers (Zikic and Ezzedeen, 2015). Furthermore, while intelligent career theory has been used in other fields such as academia (Beigi, Shirmohammadi, and Arthur, 2018;, executives (Guptill, Reibling, and Clem, 2018;Lee, 2018), expatriates (Cappellen and Janssens, 2008) and other professionals (Beigi, Nayyeri, and Shirmohammadi, 2020;Blokker, Akkermans, Tims, Jansen, and Khapova, 2019;Haenggli and Hirschi, 2020;Schlosser, Lam, and Kerr, 2021), and mostly found empirical backing for numerous career competencies and relevant resources in influencing career success in all its forms, there is a vacuum about the context of entrepreneurs. This especially refers to knowing whom, why, and how, which are prominent in the new career literature but are glaringly ignored by most research in the entrepreneurship area Crowley-Henry, O'Connor, and Suarez-Bilbao, 2021;Schlosser et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while intelligent career theory has been used in other fields such as academia (Beigi, Shirmohammadi, and Arthur, 2018;, executives (Guptill, Reibling, and Clem, 2018;Lee, 2018), expatriates (Cappellen and Janssens, 2008) and other professionals (Beigi, Nayyeri, and Shirmohammadi, 2020;Blokker, Akkermans, Tims, Jansen, and Khapova, 2019;Haenggli and Hirschi, 2020;Schlosser, Lam, and Kerr, 2021), and mostly found empirical backing for numerous career competencies and relevant resources in influencing career success in all its forms, there is a vacuum about the context of entrepreneurs. This especially refers to knowing whom, why, and how, which are prominent in the new career literature but are glaringly ignored by most research in the entrepreneurship area Crowley-Henry, O'Connor, and Suarez-Bilbao, 2021;Schlosser et al, 2021). Despite the intelligent career framework's theoretical appeal and practical applicability, much empirical work continues to focus on career success as measured from an organisational viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, whilst intelligent career theory has been used in other fields such as academia (Beigi et al , 2018; El-Baroudi and Khapova, 2021), executives (Guptill et al , 2018; Lee, 2018), expatriates Cappellen and Janssens (2008) and other professionals (Beigi et al , 2020; Blokker et al , 2019; Haenggli and Hirschi, 2020; Schlosser et al , 2021) and mostly found empirical backing for numerous CC and relevant resources in influencing CS in all its forms, there is a vacuum in the context of entrepreneurs. This especially refers to knowing whom, why and how, which are prominent in the new career literature but are glaringly ignored by most research in the entrepreneurship area (Ayoobzadeh, 2021; Crowley-Henry et al , 2021; Schlosser et al , 2021). Further, despite the intelligent career framework’s (ICF) theoretical appeal and practical applicability, much empirical work continues to focus on CS as measured from an organisational viewpoint.…”
Section: Introductionmentioning
confidence: 99%